Effects of a 7-week active breaks intervention program on physical literacy and body mass index - Urbano-Mairena, Javier; Muñoz-Bermejo, Laura; Carlos-Vivas, Jorge; Pastor-Cisneros, Raquel; Montenegro-Espinosa, José Adrián; Mendoza-Muñoz, María (Frontiers in Psychology, 2025)
IntroductionPhysical literacy (PL) emerges as a highly effective resource for creating lasting physical activity habits at a time when physical inactivity has become one of the main risk factors in our population. Thus, active breaks (AB) could be an ideal option for increasing physical activity time in schoolchildren.MethodsA cross-sectional quasi-experimental study was conducted, involving 89 participants aged 8-12 years from Extremadura. The Canadian assessment of physical literacy (CAPL-2) was administered to assess the participants' physical literacy level. The BMI was also measured.ResultsHigher scores were obtained in all domains and subdomains of the CAPL in the experimental group. Significant differences were found both in total physical literacy score (p < 0.001) and in all domains and subdomains, except for the subdomains self-reported question, intrinsic motivation and knowledge and understanding domain (p = 0.344).ConclusionThe results of the study support the positive effects of an AB program of PL and its domains. The development of active break programs could help to increase the PL level of schoolchildren.